PERANCANGAN SISTEM MONITORING PENDETEKSI KEBOCORAN GAS PADA TABUNG LPG MENGGUNAKAN SENSOR MQ2 BERBASIS INTERNET OF THINGS RUMAH MAKAN PADANG MMB - Rizki Fauzi; Joko Suwarno (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
LPG gas is one of the government's conversion programs into modern household goods today. Although LPG gas is more practical to use than kerosene, it still has drawbacks, namely the dangers that LPG gas can cause in the event of a gas leak. The LPG (Liquefied Petroleum Gas) gas leak detection and monitoring system is an anticipatory step to deal with hazards such as gas cylinder explosions. There are many incidents where a building explodes because the occupants are negligent in anticipating that there will be no gas leak. This project describes how to build a detection system with the MQ-2 sensor with the ESP8266 Microcontroller, the data obtained is then uploaded to a server so that leak notifications can be accessed from anywhere. This system gets a standard value of a room without leakage from 0 to 500 and is able to detect leaks with an LPG gas content of 600 to 1000 within 10 minutes and reports continuously at 1 minute intervals. And this system has complied with the rules of the Internet of things.